Robert Feulgen Lecture | LAMINS IN NUCLEAR ORGANISATION AND CHROMATIN REGULATION (European Journal of Histochemistry)
Lamins form a filamentous network at the nuclear envelope that anchors heterochromatin and repressed genes to the nuclear periphery. Lamin A also exists as a non-filamentous pool in the nuclear interior, where it interacts with lamin-associated polypeptide 2 alpha (LAP2a). Both proteins associate with euchromatin containing active genes, but the functional significance for gene regulation is poorly understood. Using an in vitro myoblast differentiation cell culture model, we found that LAP2a relocates towards genomic regions containing myogenic genes in early stages of muscle differentiation, facilitating efficient myogenic gene expression, while lamins mostly associate with regions apart from these genes. Strikingly, upon depletion of LAP2a, A-type lamins spread across active chromatin and accumulate at regions of active H3K27ac and H3K4me3 histone marks in the vicinity of myogenic genes, leading to their impaired expression during differentiation. Reorganization of A-type lamins towards the active, gene rich chromatin regions is accompanied by depletion of the active chromatin mark H3K27ac and a significantly impaired myogenic differentiation. Thus, the interplay of LAP2a and A-type lamins is crucial for efficient expression of myogenic genes. While most of these genes are located in the nuclear interior, MyoD1, a master regulator of myogenesis is located at the nuclear periphery in proliferating myoblasts, but it is transcriptionally active. We developed a myoblast reporter cell line to detect the nuclear position of MyoD1 in live cells, in order to identify mechanisms involved in anchoring MyoD1 to the nuclear periphery. Knockout of lamin A caused detachment of heterochromatin from the nuclear periphery but did not affect the peripheral MyoD1 localization. In contrast, depletion of the ERand nuclear envelope protein WFS1 released MyoD1 into the nuclear interior. Genome wide chromatin interaction studies showed that WFS1 interacts with active MyoD1 enhancer sequences. Thus, while peripheral lamins bind to repressed genes, WFS1 anchors active genes to the nuclear envelope allowing their efficient expression.